1000 Action Words (Yellow) - Shama Zain (Karachi Paramount Pvt Ltd, 2023)
Paramount 1000 Words Series is a collection of three delightful books designed for young and curious minds. The basic purpose of developing this series is to help kids discover the world. Children will learn by exploring themself and the environment around them. These books consist of objects and scenarios related to a child$1 (Bs day-to-day life, surroundings, neighborhood, and outer world. All the books are accompanied by eye-catching pictures & illustrations, arranged in a visually appealing way to grab the attention of readers. Children will be able to analyze the pictures to understand the meaning and concept of each word. These books will also help the kids to expand their vocabulary by learning new words. Interesting themes and characters are designed to make learning fun. Different activities are included to make the children think more deeply.s